Analyzing Lab and Field Compaction Methods for designing Roller Compacted Concrete Pavements (RCCP) with Different Curing Processes: Articles - Hassoon, Hussein Raheem; Abbas, Zena K. (Engineering, Technology & Applied Science Research, 2024)
Roller-Compacted Concrete Pavements (RCCP) display a combination of attributes associated with both asphalt and conventional rigid pavements. However, their broader implementation remains constrained. One of the reasons is the discrepancy between the manner in which the RCCP mixture behaves in a laboratory setting and its performance in the field. In laboratory settings, the RCCP is blended in accordance with the modified Proctor approach. Subsequently, the Vibratory Hammer (VH) technique is employed to create specimens for strength characterization. In contrast, the actual pavement is constructed using a variety of rollers, including static, pneumatic, and vibratory types. Additionally, specimens are extracted from the actual pavements and compared to laboratory values to ensure quality control. The usage of diverse compaction mechanisms and energies throughout these procedures gives rise to discrepancies between field and laboratory behavior, necessitating a comprehensive understanding. This investigation examines the various techniques for designing RCCP, including the VH, Vibratory Table (VT), and Manufactured Roller (MR), which have been developed and utilized by previous researchers. These techniques are then compared to Field Specimens (FS). Furthermore, the RCCP is treated with three distinct curing methods: normal curing, coating the mixture with waterproof material, and spraying with water. The compressive strength of the RCCP has been sensitive to both the compaction method employed and the curing process. Additionally, research has indicated that the MR technique may be a viable option for the RCCP design. However, it is essential to optimize this technique to ensure an accurate simulation of the field conditions.